Teachers' Views Regarding the Character of Students' Perseverance in Science Learning - Sukarno, Sukarno; Win, Khin Tan; Hong, Dong Anh Chi (Integrated Science Education Journal, 2024)
Purpose of the study: The primary objective of this research was to describe teachers' views regarding the importance of students' persistent character in learning science when teaching class VII students at Junior high school. Methodology: This research used the qualitative Miles and Huberman method with a sample of 1 teacher representing 3 science teachers at Junior high schools in Indonesia, Myanmar, and Vietnam. Researchers conducted interviews with science teachers. The sampling technique used was purposive sampling. Research data was taken using the interview method. The data analysis used is the results of interviews linked to theories from various literature. Main Findings: The findings of this research show that the results of teacher interviews at Junior high school, teachers said that persistence plays an important role in creating an effective learning environment. Students who have a high level of perseverance will achieve better results in understanding complex science concepts and prepare students who are tough and never stop learning. Novelty/Originality of this study: The benefit of this research is to know the importance of students' persistent character in understanding science learning. Hopefully, future researchers will be better off adding student and teacher research methods as samples and questionnaires or question research instruments. This aims to understand better the character development indicators of student persistence in learning.